PENGARUH PADAT TEBAR TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS KOKI (Carassius auratus) SISTEM RESIRKULASIPENGARUH PADAT TEBAR TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS KOKI (Carassius auratus) SISTEM RESIRKULASI - Saputra, Reza Deska; Firman; Martudi, Suharun; Firman, Firman (University of Prof. Dr. Hazairin, SH, 2023)
The research aimed to obtain the best stocking density for goldfish (Carassius auratus) which are kept using a recirculation system. The research was conducted for 60 days from March to May 2023 at Durian street, Bengkulu City. The research used a Completely Randomized Design (CRD) consisted of 4 stocking density treatments and 6 repetitions so it’s obtained 24 experimental units. The treatments consisted of stocking density of 15 fish/20 liters (P1), 30 fish/20 liters (P2), 45 fish/20 liters (P3), and 60 fish/20 liters (P4). The research used container in the form of plastic box measuring 50 cm x 30 cm x 30 cm. The results showed that stocking density had a very significant effect on biomass weight growth and specific growth rate, but had no significant effect on absolute length and survival rate. The stocking density of 60 fish/20 liters (P4) resulted biomass weight growth of 131.23 grams, survival rate of 99.00 percent, daily biomass weight growth of 2.45%, and length growth of 2.64 cm.